Faial Building: Formal analysis of a modern heritage in the Historic Center of the city of Porto Alegre-RS - Domingues, Quétilan Rodrigues; Souto, Ana Elisa Moraes (National Journal of City Management, 2025)
Objective - This article aims to conduct a design investigation on the Faial Building (1962), one of Emil Bered's works, located in the Historic Center of Porto Alegre-RS.Methodology - The investigation was conducted based on analyses of the site, considering the immediate surroundings, formal analyses that include the architectural concept and design solutions, in addition to a brief reflection on possible inspirations that guided some of the solutions present in the Faial Building.Originality/relevance - The study is part of research lines focused on heritage architecture and contributes to the dissemination of knowledge that fights for recognition and preservation within large urban centers, the preservation of modern built heritage.Results - The research allowed us to understand the main solutions explored by Emil Bered in this work, as well as the way in which the building integrates with its surroundings.Theoretical/methodological contributions - The methods applied contribute to future research, since they can be easily reproduced in other examples of modern architecture.Social and environmental contributions – The study is relevant in presenting to the academic community and society an important example of modern architecture in Rio Grande do Sul, aiming at the conservation of a heritage site and preservation of an inhabited building, but in a state of poor conservation.
Keywords: Faial Building; Modern architecture; Historical heritage; Architect Emil Bered